P-wave dispersion in panic disorder - Yavuzkir, Mustafa; Atmaca, Murad; Dagli, Necati; Balin, Mehmet; Karaca, Ilgin; Mermi, Osman; Aslan, I. Nadi (Lippincott Williams & Wilkins, 2007)
Background: P-wave dispersion (PWD) is defined as the difference between the maximum and the minimum P-wave (Pmax and Pmin, respectively) duration. Significant variation in cardiac atrial PWD has been correlated with changes in systemic autonomic tone such as during periods of anxiety. It is also known that the degree of PWD seen on 12-lead electrocardiogram (ECG) may be a predictor of susceptibility of the atrial myocardium to future atrial fibrillation (AF). Therefore, we firstly aimed to show an association between PWD and panic disorder, a state of high sympathetic tone. Methods: PWD was measured in 40 outpatients with panic disorder and in 40 physically and mentally healthy age- and gender-matched controls. In addition, the Panic Agoraphobia Scale (PAS) and the Hamilton Depression Rating Scale (HDRS) were scored concomitantly. Results: Both Pmax and Pmin were significantly higher than those of healthy controls. PWD was significantly greater in the panic disorder group than in the controls. As expected, the mean score on PAS was significantly higher for the panic disorder group than for the controls and correlated significantly with PWD. Heart rate (measured as RR intervals in milliseconds on electrocardiogram) did not differ significantly between the groups. Conclusions: The findings of the present study suggest that the disorder may be associated with an increase in PWD. This association may result from prolonged anxiety and increase in sympathetic modulation, which are main characteristics of panic disorder.
Keywords: P-wave dispersion; panic disorder; anxiety